2019
DOI: 10.20937/rica.2019.35.01.16
|View full text |Cite
|
Sign up to set email alerts
|

Remoción De Colorantes Azo Con Alginato: Relación Entre Estructura De Colorante Y Eficiencia De Remoción

Abstract: Palabras clave: agregación, grupos funcionales, gelificación RESUMEN Los colorantes azo representan entre 60 y 75 % de los colorantes producidos actualmente. Se utilizan ampliamente en la industria cosmética, del papel, optoelectrónica, textil, etc. Desafortunadamente una vez utilizados, debido a su alta resistencia a tratamientos convencionales de aguas residuales, contaminan los cuerpos de agua donde son descargados. En este reporte se utiliza alginato de sodio (ALG) para remover los colorantes azo rojo dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…(3) The adsorption energy does not depend on the surface covered by adsorbate molecules The Pec-Ca-DR80 system does not satisfy the above assumptions. For example, [37] reported that the attachment of the first dye molecule to the adsorbent promoted the formation of aggregates on the adsorbent surface. This is attributed to aromatic rings and other functional groups of the dye molecules, which generate molecular planarity and lead to the formation of H-type aggregates [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…(3) The adsorption energy does not depend on the surface covered by adsorbate molecules The Pec-Ca-DR80 system does not satisfy the above assumptions. For example, [37] reported that the attachment of the first dye molecule to the adsorbent promoted the formation of aggregates on the adsorbent surface. This is attributed to aromatic rings and other functional groups of the dye molecules, which generate molecular planarity and lead to the formation of H-type aggregates [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of hydrogen bonds between DB and chitosan chains, due to the partial deprotonation of amino groups, cannot be excluded, indicating that the driving force of the adsorption process was not only attributable to electrostatic interactions but also to hydrogen bonds and hydrophobic interactions. To infer more information, the IR spectrum of DB was collected [see Figure (a)], and the detailed description is reported in the Supporting Information. Unfortunately, the typical bands of DB were not detected in the chitosan blended films [Figure (b,c)], and this behavior could be ascribed to two factors.…”
Section: Resultsmentioning
confidence: 99%
“…The Zimm-Bragg model has been applied and reported as an adsorption model by our group [32]. In this work, the theoretical parameters of the Zimm-Bragg model, K u and U (nucleation and cooperativity parameters, respectively), were obtained by using the nonlinear regression method in the experimental isotherms.…”
Section: Methodsmentioning
confidence: 99%